Analisis Tingkat Kebugaran Jasmani Siswa Kelas Atas Ditinjau Dari Keikutsertaan Dalam Ekstrakurikuler - Fajar Bahari; Yulingga Nanda Hanief; Slamet Junaedi (Jendela Olahraga, 2020)
It is not yet known the level of physical fitness of students who take extracurricular sports in SDN 2 Plemahan is the background of this study. The formulation of the problem taken is: What is the level of physical fitness of upper-class students at SDN 2 Plemahan?. This research is a quantitative descriptive study with survey techniques. The sample used upper-class students who participated in extracurricular basketball, volleyball, futsal, martial arts as many as 44 children. The research instrument used the Indonesian Physical Fitness Test (TKJI), namely the 40-meter Running test, the elbow hanging, lying down, upright jumping, running 600 meters. The data analysis technique uses percentage analysis with the TKJI norm. The results of this study are: (1) The level of physical fitness of basketball extracurricular upper-class students falls into the medium category (2) The level of physical fitness of upper-class extracurricular volleyball clubs falls into the medium category, (3) The level of physical fitness of upper-class students futsal extracurricular entry in the medium category (4) The level of physical fitness of pencak silat extracurricular upper-class students falls into the medium categoryKeywords: Physical fitness, Student, Upper-class, Extracurricular, Sports AbstrakBelum diketahui tingkat kebugaran jasmani siswa yang mengikuti ekstrakurikuler olahraga di SDN 2 Plemahan menjadi latar belakang penelitian ini. Rumusan masalah yang diambil adalah: Seberapakah tingkat kebugaran jasmani siswa kelas atas SDN 2 Plemahan?. Penelitian ini merupakan penelitian deskripsitif kuantitatif dengan teknik survei. Sampel menggunakan siswa kelas atas yang mengikuti ekstrakurikuler bolabasket, bolavoli, futsal, pencak silat sebanyak 44 anak. Instrumen peneltian menggunakan Tes Kebugaran Jasmani Indonesia (TKJI) yaitu tes Lari 40 meter, Gantung siku, baring duduk, loncat tegak, lari 600 meter. Teknik analisis data menggunakan analisis persentase dengan norma TKJI. Hasil penelitian ini adalah: (1) Tingkat kebugaran jasmani siswa kelas atas ekstrakurikuler bola basket masuk dalam kategori sedang (2) Tingkat kebugaran jasmani siswa kelas atas ekstrakurikuler bolavoli masuk dalam kategori sedang, (3) Tingkat kebugaran jasmani siswa kelas atas ekstrakurikuler futsal masuk dalam kategori sedang (4) Tingkat kebugaran jasmani siswa kelas atas ekstrakurikuler pencak silat masuk dalam kategori sedangKata kunci: Kebugaran jasmani, Siswa, Kelas atas, Ekstrakurikuler, Olahraga